Measurement of the angular correlation between the two gamma rays emitted in the radioactive decays of a 60Co source with two NaI(Tl) scintillators. (1st September 2022) - Amato, E C; Anelli, A; Barbieri, M; Cataldi, D; Cellamare, V; Cerasole, D; Conserva, F; De Gaetano, S; Depalo, D; Digennaro, A; Fiorente, E; Gargano, F; et al.
Abstract: We implemented a didactic experiment to study the angular correlation between the two gamma rays emitted in typical 60 Co radioactive decays. We used two NaI(Tl) scintillators, already available in our laboratory, and a low-activity 60 Co source. The detectors were mounted on two rails, with the source at their center. The first rail was fixed, while the second could be rotated around the source. We performed several measurements by changing the angle between the two scintillators in the range from 90° to 180°. Dedicated background runs were also performed, removing the source from the experimental setup. We found that the signal rate increases with the angular separation between the two scintillators, with small discrepancies from the theoretical expectations.